Implementation of European Cohesion Policy at the sub‐national level: Evidence from beneficiary data in Eastern Germany. Issue 1 (9th January 2018) - Dettmer, Bianka; Sauer, Thomas
Abstract: Regional governments' discretion in allocating structural funds is limited by the competences of the European Commission to control fiscal activities of decentralized governments. Regional political behaviour and the complexity of the implementation process shape the policy outcome. Who benefits from structural funds? In this paper, we analyse implementation of ERDF funds in East Germany in the financial perspective 2007 to 2013. We find that less rural regions and some economic sectors benefit by more than others. A few beneficiaries control the highest share of the funds. The Gini coefficients vary by group of actor and show high inequality in the distribution of the funds. This indicates that a few actors have better access to the funds than others.